Using Intelligent Building Energy Management System for the Integration of Several Systems to one Overall Monitoring and Management System. (March 2017) - Papantoniou, Sotiris; Mangili, Stefano; Mangialenti, Ivan
Abstract: In the CommONEnergy project the interoperation and optimization of active systems in shopping malls is performed by using an intelligent Building Energy Management System (iBEMS) which integrates open communication protocols for speaking with several industrial systems. The iBEMS assures the communication of several systems using open communication protocols in order to transfer the required information while on the same time provides a Human to Machine Interface (HMI) for the control and monitoring of the connected systems. In parallel the iBEMS stores historical values for future comparison of the performance. With the operation of the iBEMS the energy manager of a building can overview in real time the operation of all the systems' components and take decisions which can assist with the proper operation. In parallel the programming routines of the iBEMS adjust automatically the operation of the systems using inputs from the installed sensors and from external data (e.g. weather forecast).